2004
DOI: 10.1175/2932.1
|View full text |Cite
|
Sign up to set email alerts
|

Definition of South China Sea Monsoon Onset and Commencement of the East Asia Summer Monsoon*

Abstract: The climatological mean summer monsoon onset in the South China Sea (SCS) is a remarkably abrupt event. However, defining onset dates for individual years is noticeably controversial. The controversies and complications arise primarily from a number of factors: the intermittent southward intrusion of cold fronts into the northern SCS, the bogus onset in late April before the establishment of tropical monsoons over Indochina, and active intraseasonal oscillation. In this paper, a simple yet effective index, U S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
325
3
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(341 citation statements)
references
References 28 publications
8
325
3
5
Order By: Relevance
“…Wang et al (2004) suggested a wind index -the 850-hPa zonal winds averaged over the region 5°-15°N, 110°-120°E (the precise domain is 3.75°-16.25°N, 108.75°-121.25°E) -to quantify changes in the SCS circulation before, during, and after the onset. The OLR data are used as a proxy for deep convection because of its strong relationship with tropical rainfall (Wu and Zhang, 1998), which is a direct reflection of the summer monsoon.…”
Section: Monsoon Onset Datementioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (2004) suggested a wind index -the 850-hPa zonal winds averaged over the region 5°-15°N, 110°-120°E (the precise domain is 3.75°-16.25°N, 108.75°-121.25°E) -to quantify changes in the SCS circulation before, during, and after the onset. The OLR data are used as a proxy for deep convection because of its strong relationship with tropical rainfall (Wu and Zhang, 1998), which is a direct reflection of the summer monsoon.…”
Section: Monsoon Onset Datementioning
confidence: 99%
“…Further, the SCSSM onset indicates the beginning of the EASM (Wang et al, 2004). An early or late SCSSM onset could affect the precipitation pattern of the EASM to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Qiao et al (2002) showed that there are huge differences in precipitation over four sub-regions (105-110 E, 0-20 N; 110-120 E, 0-5 N; 110-120 E, 5-10 N; 110-120 E, 10-20 N), and the precipitation over the region of 110-120 E and 10-20 N can best represent the summer monsoon precipitation over the South China Sea. Wang et al (2004) also suggested that the rainfall averaged over the same region can be used as a rainfall index to describe the SCSSM onset because it increases concurrent with the reversal of the 850 hPa zonal. Therefore, we will choose 110-120 E and 10-20 N as our computation and analysis domain.…”
Section: Methodsmentioning
confidence: 99%
“…Its onset and intraseasonal variability, however, are the focus in the recent years (Chang and Chen 1995;Wang et al 2004;Mao and Chan 2005). With the field observation of the South China Sea Monsoon Experiment (SCSMEX) in 1998, much better data were collected for the studies of the SCSSM (Lau et al 2000;Ding et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For those that successfully predict a variety of atmospheric conditions associated with monsoons [e.g., Wang et al, 2009], skill in predicting monsoon rainfall is insignificant. In lamenting the failures to predict monsoon failures in and 2004, Gadgil et al [2005 argued that no progress in monsoon prediction had been made for seven decades and stated: "It is clear that no 'quick fix' solutions are available to tackle the problem of predicting the summer monsoon rainfall over the Indian region. "…”
Section: Introductionmentioning
confidence: 99%